A shared regulatory perspective on deferral from blood donation of men who have sex with men (MSM)1. Issue 4 (13th June 2014) - Epstein, J.; Ganz, P. R.; Seitz, R.; Jutzi, M.; Schaerer, C.; Michaud, G.; Agbanyo, F.; Smith, G.; Prosser, I.; Heiden, M.; Saint‐Marie, I.; Oualikene‐Gonin, W.; et al.
<x xml:space="preserve">Abstract</x> National Regulatory Authorities (NRAs) establish deferral criteria for donors with risk factors for transfusion transmissible infections (TTI). In most jurisdictions, epidemiological data show that men who have sex with men (MSM) have a significantly higher rate of TTI than the general population. Nevertheless, changes from an indefinite donor deferral for MSM have been considered in many countries in response to concerns over a perceived discrimination and questioning of the scientific need. Changes to MSM donor deferral criteria should be based on sound scientific evidence. Safety of transfusion recipients should be the first priority, and stakeholder input should be sought.